Reduction in the olfactory ability in aging Mitf mutant mice without evidence of neurodegeneration - Mechmet, Fatich; Steingrímsson, Eiríkur; Petersen, Petur Henry (Frontiers in Aging, 2024)
Age-related decline occurs in most brain structures and sensory systems. An illustrative case is olfaction. The olfactory bulb (OB) undergoes deterioration with age, resulting in reduced olfactory ability. A decline in olfaction is also associated with early symptoms of neurodegenerative diseases, including Alzheimer’s disease (AD) and Parkinson’s disease (PD). However, the underlying reasons are unclear. The microphthalmia-associated transcription factor (MITF) is expressed in the projection neurons (PNs) of the OB–the mitral and tufted (M/T) cells. Primary M/T cells from Mitf mutant mice show hyperactivity, potentially attributed to the reduced expression of a key potassium channel subunit, Kcnd3/Kv4.3. This influences intrinsic plasticity, an essential mechanism involving the non-synaptic regulation of neuronal activity. As neuronal hyperactivity often precedes neurodegenerative conditions, the current study aimed to determine whether the absence of Mitf causes degenerative effects during aging. Aged Mitf mutant mice showed reduced olfactory ability without inflammation. However, an increase in the expression of potassium channel subunit genes in the OBs of aged Mitfmi-vga9/mi-vga9 mice suggests that during aging, compensatory mechanisms lead to stabilization.